SOSIALISASI PROFESI DI INDUSTRI TEKNOLOGI INFORMASI DALAM MENGANTISIPASI TANTANGAN PELUANG DI ERA DIGITAL - Sudarno Wiharjo; Mardiyanto; Nilovar Asyiah (Abdi Jurnal Publikasi, 2025)
In the digital era, information technology has become a key pillar across various aspects of life, including the world of work. Rapid developments in artificial intelligence, big data, cloud computing, and the Internet of Things (IoT) have driven significant changes in labor demands. However, a lack of understanding about careers in the technology industry and the gap between education and industry needs remain major challenges. Career awareness programs in the field of technology are essential to help individuals understand the diverse career opportunities, required skills, and existing challenges. The technology sector offers a wide range of professions such as software engineer, data scientist, cybersecurity analyst, and cloud engineer—each requiring specialized expertise. While the demand for technology professionals continues to rise, intense competition and rapid technological advancements demand continuous learning and adaptability. Key challenges in this industry include high work pressure, cybersecurity regulations, and maintaining a work-life balance. Therefore, beyond technical skills, time management, communication, and problem-solving abilities are also crucial. Collaboration among educational institutions, government, and industry is necessary to provide relevant insights and training that prepare the workforce for future demands. This community service program aims to enhance public understanding of technology-related professions, equip participants with essential digital skills, and assist them in designing effective career strategies. Through this approach, more individuals are expected to seize opportunities in the tech industry and contribute to innovations that benefit society.